(untitled) (Hekima Review, 2020)
This reflection treats the author’s personal missionary journey in Africa in the context of the 50 Year anniversary (1970 to 2020)of Orbis Books, the Catholic religious publishing house of the Mary knoll Missionary Society. Topics include: the author’s four Orbis books; African and Africanists Authors of Orbis Books; other key Orbis Books; the author’s participation in the Orbis Books Advisory Committee; the author’s friendships with African Orbis Authors; African Conversation Theology: a Distinct Theological Method; and going digital in religious publishing. The reflection concludes with possible themes for Orbis Books on African Christian Theology in the next 50 years (2020 to 2070).